Understanding and Targeting HBV Transcription and Post-Transcriptional Regulation - Simon P. Fletcher; Rudolf K. Beran (Viruses)
Chronic hepatitis B (CHB) affects approximately 300 million people worldwide and current therapies rarely cure it [...]